Role of interleukin-8 in odontogeneic differentiation of stem cells from human exfoliated deciduous teeth cultured on human amniotic membrane - Zahari, Wafa' (2018)
Interleukin-8 (IL-8), an inflammatory cytokine with pleiotropic biological effects, has been reported to be implicated in odontogenesis and involved in odontoblast-mediated immune responses. However, the exact mechanism on how IL- 8 influences odontogenesis remains unclear. Hence, this study was conducted to investigate the role and mechanism of IL-8-immunomodulatory pathway in the differentiation of stem cells from human exfoliated deciduous teeth (SHED) into odontoblast-like cells. SHED were seeded on human amniotic membrane (HAM) and treated with bone morphogenetic protein-2 (BMP-2). Four groups were assigned: SHED only (S), SHED with BMP-2 (SB), SHED on amniotic membrane without BMP-2 (SA), SHED on amniotic membrane with BMP-2 (SAB). Following treatment, SHED were harvested on day 1, 7, 10 and 14, and odontogeneic differentiation potential was assessed by the expression of odontogeneic markers using reverse transcriptase polymerase chain reaction and calcium deposition by Alizarin Red S staining. Thereafter, the optimal concentration of reparixin and rhIL-8 were determined using Real Time RT-PCR. For IL-8 study, another four groups were assigned; SHED on amniotic membrane with BMP-2 (SAB), SHED on amniotic membrane with BMP-2 and reparixin (SABR), SHED on amniotic membrane with BMP-2 and rhIL-8 (SAB8), SHED on amniotic membrane with BMP-2, reparixin and rhIL-8 (SABR8). SHED were treated with reparixin as IL-8 inhibitor, while recombinant human IL-8 (rhIL-8) as IL-8 inductor, and downstream analysis were conducted using Real Time RT-PCR. The levels of IL-8 protein secretion of SHED with and without IL-8 induction and inhibition during odontogeneic differentiation was analysed using ELISA. The effect of IL-8 in calcium deposition of SHED was determined using Alizarin Red S staining. Results of the present study showed that odontoblast specific gene markers DSPP, DMP1, OPN were highly expressed on day 7 onwards as odontogeneic differentiation occurred. On the other hand, the BMP-2 and COL-1 expressions remain lowly expressed. The optimal concentration for reparixin and rhIL-8 were found to be 50 nM and 0.01 ng/ml, respectively. For IL-8 downstream pathway analysis, PI3K/AKT/mTOR and JAK2/STAT3 signalling pathways were suggested to be involved in odontogeneic differentiation as the expression of all the markers were high, whereas inhibition of IL-8 using reparixin caused significant reduction of their expression. NF-κB expression showed relatively low expression in all samples when compared to other genes suggesting that NF-κB signalling plays a minor role in odontogeneic differentiation. In addition, upregulation of DSPP, DMP1 and OPN expression, and higher intensity of alizarin staining were observed when SHED were inhibited with reparixin (SABR) suggested odontogeneic differentiation has occurred. However, no significant changes were observed in the expression of odontoblast markers and SHED mineralisation when SHED were induced with rhIL-8. In conclusion, this study suggests that inhibition of IL-8 receptor by reparixin promotes odontogeneic differentiation of SHED when cultured on HAM treated with BMP-2.